Does Profitability Mediate the Influence of Corporate Social Responsibility on Stock Prices in ESG-Leading Firms in Indonesia? - Dwitama, Ellisia; Tannia, Tannia (Dinasti International Journal of Management Science, 2024)
This research aims to analyze whether profitability mediates the influence of corporate social responsibility on stock prices in ESG Leading firms in Indonesia. The sample for this study is 14 companies listed in IDXESGL during 2020–2022. In this quantitative study, path analysis of data panels using Eviews 12. The study's findings suggest that CSR and ROA have a significant influence on stock prices. However, ROA is not influenced by CSR, and ROA cannot act as a mediator for CSR in influencing stock prices. The study's findings provide businesses and stakeholders with insight that CSR is a long-term initiative that will eventually help both businesses and society. Penelitian ini bertujuan menganalisis apakah profitabilitas menjadi mediator dalam pengaruh corporate social responsibility terhadap harga saham pada perusahaan ESG Leaders di Indonesia. Sampel terdiri dari 14 perusahaan yang terdaftar di IDXESGL selama 2020–2022. Dalam studi kuantitatif, analisis jalur data panel menggunakan Eviews 12. Temuan menunjukkan bahwa CSR dan ROA berpengaruh signifikan terhadap harga saham. Namun, CSR tidak mempengaruhi ROA, dan CSR tidak berpengaruh signifikan terhadap harga saham melalui ROA. Temuan ini memberikan wawasan kepada bisnis dan pemangku kepentingan bahwa CSR merupakan inisiatif jangka panjang yang akan memberikan manfaat bagi bisnis maupun masyarakat.